DETERMINATIONS OF PROFITABILITY IN THE AGRICULUTRAL SECTOR IN SERBIA - Milošev, Ivana (Economics of Agriculture, 2023)
This research paper considers performance determinants at firm and industry level from the perspective of agricultural industry since this industry is recognized as one of key drivers of Serbian national economy. Sample is consisted of 115 large and medium-sized firms as they participate around 50% in total sector turnover, during years 2017 - 2021. The Generalized Method of Moments was used to analyze how firm factors (lagged profitability, leverage, labor cost, size, liquidity, sales growth) and industry factors (market share and capital intensity) affect profitability. Research results showed that profitability is strongly positively affected by its past values and stronlgy negatively affected by leverage, labours costs and industry factor capital intensity. The results suggest that internal factors are key determinants of the performance of agricultural firms rather than external factors and that leverage is the most significant determinant of profitability therefore managers should pay more attention to debt policy.